Summer pastures: between “commons” and “public goods” - Corinne Eychenne; Lucie Lazaro (Revue de Géographie Alpine)
In the Pyrenees, the collective nature of the appropriation and management methods of pastoral resources make them one of the rare surviving examples in France of governance as commons, as described in the work of E. Ostrom. However, other users of the mountains, tend to see pastoral areas as spaces that are “open to everyone”, providing tangible and intangible public goods (landscape, biodiversity, nature, liberty…). In this article we question the ways in which government deals with pastoral activity, focussing on its complex status, between common good and public good. This analysis provides the opportunity to call into question an approach to pastorality seen solely through an external view of pastoral activity. On the contrary, we believe that there is an “internal” pastorality in which the collective dimension of the appropriation and the use of pastoral resources provides one of the foundations for the sense of social belonging and development of identity for farmers practising transhumance.